The digital revolution and governance in Brazil: Evidence from participatory budgeting. Issue 2 (3rd April 2019) - Touchton, Michael; Wampler, Brian; Spada, Paolo
ABSTRACT: Cities have initiated e-participation programs to cut costs, promote transparency and engage more citizens in recent years. Participatory budgeting (PB) is a democratic innovation that is said to enhance governance and empower citizens. We test hypotheses surrounding why cities use electronic vs. traditional forms of PB as well as variation in policy outcomes generated by the use of different PB types. Our data are from an original survey of 94 administrators of Brazilian PB programs. Our results provide new evidence on e-participation in Latin America and a new direction for scholarship on the digital revolution in the developing world.